MORPHOLOGY AND BIOECOLOGY OF SITONA CYLINDRICOLLIS (FAHRAEUS, 1840) AMONG THE REPRESENTATIVES OF THE FABACEAE FAMILY (Scientific journal of the Fergana State University, 2025)
A study was conducted from March to September to investigate the distribution, morphology, and bioecology of the Curculionidae family representatives in the Fergana Valley. As a result of the research, the distribution of Sitona cylindricollis (Fahraeus, 1840) among leguminous plants in the Fergana Valley was identified, and its morphology and bioecology were studied. The study was carried out in alfalfa and chickpea agrobiocenoses in the Fergana and Namangan regions. This article presents a review of the studies conducted on the distribution, morphology, and bioecology of Sitona cylindricollis (Fahraeus, 1840) in the Fergana Valley.